EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES WITH MODELS SNOWBALL THROWING IN CLASS XI SMA NEGERI 1 JULY BIREUEN DISTRICT - Iskandar Iskandar (Jurnal Scientia, 2022)
This research is entitled the application of the Snowball Throwing learning model in improving student learning outcomes in KD Analyzing Indonesia's strategic position as the World's maritime axis in class XI SMA Negeri 1 Juli, Bireuen Regency. This study aims to find out how to improve student learning outcomes through the Snowball Throwing learning model in KD. Analyzing Indonesia's strategic position as the world's maritime axis in class XI SMA Negeri 1 Juli, Bireuen Regency. The research method, the approach that researchers use is a qualitative approach to the type of classroom action research. Data collection techniques used are tests, observations, and field notes. Data were analyzed by calculating student absorption, the percentage of teacher and student activity, and the percentage of student responses to ongoing learning. The results of the research, this research was conducted in two cycles where in the first cycle many students had not completed it and had to proceed to cycle II. This can be seen in terms of results in the implementation of the first cycle test 60% of students passed and increased in cycle II to 85% of students getting a score of ≥ 75 with an increase percentage reaching 25%. Thus, the implementation of cycle II has been successful. Based on the results of the research that has been carried out, it is concluded that the application of the Snowball Throwing learning model can improve the learning outcomes of class XI students of SMA Negeri 1 Juli in KD Analyzing Indonesia's strategic position as the world's maritime axis.